Pliocene granodioritic knoll with continental crust affinities discovered in the intra-oceanic Izu-Bonin-Mariana Arc: Syntectonic granitic crust formation during back-arc rifting - Tani, K.; Dunkley, Daniel; Chang, Q.; Nichols, A.; Shukuno, H.; Hirahara, Y.; Ishizuka, O.; Arima, M.; Tatsumi, Y. (Elsevier BV, 2015)
A widely held hypothesis is that modern continental crust of an intermediate (i.e. andesitic) bulk composition forms at intra-oceanic arcs through subduction zone magmatism. However, there is a critical paradox in this hypothesis: to date, the dominant granitic rocks discovered in these arcs are tonalite, rocks that are significantly depleted in incompatible (i.e. magma-preferred) elements and do not geochemically and petrographically represent those of the continents. Here we describe the discovery of a submarine knoll, the Daisan-West Sumisu Knoll, situated in the rear-arc region of the intra-oceanic Izu-Bonin-Mariana Arc. Remotely-operated vehicle surveys reveal that this knoll is made up entirely of a 2.6 million year old porphyritic to equigranular granodiorite intrusion with a geochemical signature typical of continental crust. We present a model of granodiorite magma formation that involves partial remelting of enriched mafic rear-arc crust during the initial phase of back-arc rifting, which is supported by the preservation of relic cores inherited from initial rear-arc source rocks within magmatic zircon crystals. The strong extensional tectonic regime at the time of intrusion may have allowed the granodioritic magma to be emplaced at an extremely shallow level, with later erosion of sediment and volcanic covers exposing the internal plutonic body. These findings suggest that rear-arc regions could be the potential sites of continental crust formation in intra-oceanic convergent margins.